Assessment of telecommunicator cardiopulmonary resuscitation performance during out-of-hospital cardiac arrest using a standardized tool for audio review. (September 2022) - Dowker, Stephen R.; Smith, Graham; O'Leary, Michael; Missel, Amanda L.; Trumpower, Brad; Hunt, Nathaniel; Herbert, Logan; Sams, Woodrow; Kamdar, Neil; Coulter-Thompson, Emilee I.; Shields, Theresa; Swor, Robert; et al.
Abstract: Objective: Telecommunicator cardiopulmonary resuscitation (T-CPR) is a critical component of optimized out-of-hospital cardiac arrest (OHCA) care. We assessed a pilot tool to capture American Heart Association (AHA) T-CPR measures and T-CPR coaching by telecommunicators using audio review. Methods: Using a pilot tool, we conducted a retrospective review of 911 call audio from 65 emergency medical services-treated out-of-hospital cardiac arrest (OHCA) patients. Data collection included events (e.g., OHCA recognition), time intervals, and coaching quality measures. We calculated summary statistics for all performance and quality measures. Results: Among 65 cases, the patients' mean age was 64.7 years (SD: 14.6) and 17 (26.2%) were women. Telecommunicator recognition occurred in 72% of cases (47/65). Among 18 non-recognized cases, reviewers determined 12 (66%) were not recognizable based on characteristics of the call. Median time-to-recognition was 76 seconds ( n = 40; IQR:39–138), while median time-to-first-instructed-compression was 198 seconds ( n = 26; IQR:149–233). In 36 cases where coaching was needed, coaching on compression-depth occurred in 27 (75%); -rate in 28 (78%); and chest recoil in 10 (28%) instances. In 30 cases where repositioning was needed, instruction to position the patient's body flat occurred in 18 (60%) instances, on-back in 22 (73%) instances, and on-ground in 22 (73%) instances. Conclusions: Successful collection of data to calculate AHA T-CPR measures using a pilot tool for audio review revealed performance near AHA benchmarks, although coaching instructions did not occur in many instances. Application of this standardized tool may aid in T-CPR quality review.